Giant modal gain coefficients in colloidal II-VI nanoplatelets - Guzelturk, Burak (2020)
Modal gain coefficient is a key figure of merit for a laser material. Previously, net modal gain coefficients larger than a few thousand cm-1 were achieved in II-VI and III-V semiconductor gain media, but this required operation at cryogenic temperatures. In this work, using pump-fluence-dependent variable-stripe-length measurements, we show that colloidal CdSe nanoplatelets enable giant modal gain coefficients at room temperature up to 6600 cm-1 under pulsed optical excitation. Furthermore, we show that exceptional gain performance is common to the family of CdSe nanoplatelets, as shown by examining samples having different vertical thicknesses and lateral areas. Overall, colloidal II-VI nanoplatelets with superior optical gain properties are promising for a broad range of applications, including high-speed light amplification and loss compensation in plasmonic photonic circuits.